ALUNOS COM DEFICIÊNCIA NO ENSINO REGULAR: E AGORA PROFESSOR, VAMOS FALAR DE INCLUSÃO? - Russo, Maria José de Oliveira (2007)
The inclusion of disabled students into the current teaching in Brazil is a movement that has been rising lately. Although advances have been noticed, because it is a process which needs conceptual, legal, and practice changes, brings itself some doubts, because of existent contradictions between the discourses that proclaim the inclusion and the Brazilian educational reality. Under the vision of the teachers, in the context of the inclusive school, there are several difficulties that the teachers are facing, in practice, with these students. Considering this, despite of the existing production in this field of research, it is necessary to go deeper into the research of this theme from the point of view of the teacher. So, this research investigates the voice and the optics of the teachers of regular classes that have students in situation of inclusion, more specifically the disable ones and deals with different aspects of the inclusion in the school quotidian and the support to the teacher as one of the necessary actions for the inclusive pedagogic practice highlighting the theorists that discourse the inclusive process. The study, of a qualitative character, was realized in four municipal Elementary schools of São Bernardo do Campo with the participation of nine teachers, four principals and four families of disabled children. Considering the analyze of the observed aspects, we can say that the teachers are searching for a re-signification of their practices, however, they need a constant support to deal with the diversity of these students.(AU)